Estimating direct and indirect effects of habitat structure on nesting field sparrows (Spizella pusilla) using structural equation models - Glass, Alex; Eichholz, Michael W. (Frontiers in Ecology and Evolution, 2023)
Due to consistent population declines across the continent, grassland birds have become a guild of high conservation and management interest. Despite a large number of studies investigating grassland bird habitat associations, we know relatively little about the mechanisms through which habitat characteristics may impact grassland birds, as these mechanisms are often assumed rather than directly tested. For this study, we estimated whether the effects of habitat structure on breeding Field Sparrows are mediated through changes in predator (snake and raccoon) abundance, alternate prey availability, or arthropod biomass using structural equation models. We found no evidence of nest survival or nest density of Field Sparrows being directly influenced by nest predator abundance, alternate prey, or arthropod biomass, although habitat characteristics associated with increased nest survival were also associated with greater arthropod biomass and reduced predator abundance. We suggest that habitat structure in our study area primarily impacts breeding Field Sparrows through direct means, such as influencing nest concealment or foraging efficiency. Our results also suggest that nest success and nest density are decoupled in our study area, so Field Sparrows may be preferentially selecting nest sites with structural characteristics that do not increase nest survival. Ultimately, our findings from this study indicate that while predator avoidance and food provisioning likely play an important role in determining nest survival for grassland birds, predator abundance and arthropod biomass may not necessarily predict predation risk and foraging efficiency to the extent that is often assumed.